AR and VR Content Integration: Project-Based Task Quality and Effect in Reading Comprehension - Wahyunengsih, Wahyunengsih; Murwantono, Didik (Universitas Islam Sultan Agung, 2024)
The learning media is evaluated in several aspects: the content, teaching methods, and preparation of the teaching and learning, as well as the effect on the student’s comprehension.This study aims to analyze the quality of the AR and VR content integration as PBT influences the students’ comprehension of reading. The mixed method was utilized in this study. Need analysis, situation analysis, and curriculum analysis were used to gather the preliminary data before assigning students of the Reading Course to conduct the project. The syllabus and guidelines for Project-Based Tasks were formulated based on the findings in the initial study. Modelling was required before the students independently work on the project. Experts evaluated the media. Then, the significance of the development project to the students’ improvement was also seen based on the statistical analysis of pre-and post-tests. Therefore, result of the expert evaluation and students pre and post-test result are major source of the data.Based on three aspects measured in learning media, course materials, teaching, and learning language, the result from the expert evaluation shows perfect scores are dominant in all aspects. The students’ scores also significantly improved in the post-test. It is highly recommended for teachers to combine AR and VR content development properly as the product of project-based tasks as the teaching and learning media.